MENINGKATAN KEMAMPUAN MEMBACA AWAL MELALUI PERMAINAN KARTU BERGAMBAR ANAK USIA 5-6 TAHUN DI PAUD KASIH IBU DESA PISANG BEREBUS KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - ', Narwida; ', Wilson; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations on early reading skills is to classify children are not able to mention the symbols of letters known. Recognize the voice initial letters of the names of objects that are nearby, said groups of images that have sound / the same initial letter, understand the relationship between sounds and letters benuk, read his own name, and write his own name. The formulation in this regard is whether the game card pictured letters can meningkatkatkan early reading skills of children aged 5-6 in early childhood tahn Mother Love Bananas Village Berebus Regency Kuantan District of Mount Toar Singingi?. This study aims to determine the increase in early reading skills through a card game hurf illustrated children aged 5-6 years in early childhood Mother Love Village Pisang Berebus Regency District of Gunung Toar Kuantan Singingi. The research method is a method of classroom action research conducted in two cycles, each cycle consisting of several stages, namely planning, action, observation and reflection. The number of subjects in this study amounted to 15 people. Data taken from the evaluation of the end of each cycle. The study involved one teacher as an observer. Based on the results obtained from the percentage of increase in the first cycle is 50.09% and increased in the second cycle is 75.18%. And thus it can be concluded that the card game pictured letters can improve early reading skills of children aged 5-6 years in early childhood Mother Love Bananas Berebus Kuantan District of Mount Toar Singingi.